Sports activity and the use of cigarettes and snus among young males in Finland in 1999-2010 - Mattila Ville M; Raisamo Susanna; Pihlajamäki Harri; Mäntysaari Matti; Rimpelä Arja (BMC, 2012)
Abstract Background Studies of the relationship between sports activity and smoking among adolescents and young adults report contradictory results. We examined the association between sports activity (intensity and type of sport) and the current use of snus (Swedish snuff), cigarette smoking, and the combined use of cigarettes and snus (dual use) among young males in Finland. Methods Data were collected from 16,746 male conscripts who completed a survey during the first days of their conscription during the years 1999-2010 (median age 19 years, response rate 95%). Main outcome measures were self-reported daily/occasional use of snus, cigarette smoking, and dual use. The association between sports activity, type of sport, and several sociodemographic background variables was assessed using logistic regression analysis. Results Over the study period (1999-2010), the prevalence of cigarette smoking decreased from 42% to 34%, while snus use increased from 5% to 12%, and dual use increased from 7% to 13% (p < 0.001). Compared with no physical activity, regular competitive sports activity (defined as high-intensity sports activity) was positively associated with use of snus (odds ratio [OR] 10.2; 95% confidence interval [CI]: 7.8-13.5) and negatively with cigarette smoking (OR 0.2; 95% CI: 0.1-0.3). When stratified by type of sport in multivariate models, ice hockey was most strongly associated with snus use (OR 1.6; 95% CI: 1.4-1.9) and dual use (OR 2.0; 95% CI 1.8-2.3) compared with those not playing ice-hockey, followed by other team sports for snus use (OR 1.5; 95% CI: 1.3-1.8) and dual use (OR 1.8; 95% CI: 1.6-2.0) compared with those not participating in other team-sports. Conclusions Our results show a clear association between snus use and intensity and type of training. Team sports were associated with increased use of snus and dual use compared with no participation in team sports. These findings should be acknowledged when planning and implementing preventive strategies.